The association of squamous cell carcinoma of the vulva and lichen sclerosus: implications for management and follow up. - Walkden, V; Chia, Y; Wojnarowska, F (1997)
All cases of biopsy proven squamous cell carcinoma (SCC) of the vulva and of lichen sclerosus (LS) presenting to a district general hospital between 1984 and 1993 were studied. Twenty-eight cases of squamous cell carcinoma of the vulva were identified from histological specimens. Histological evidence of LS was found in 28.5% and clinical LS in 57%. There was poor correlation between clinical and histological findings when SCC arose on a background of LS. A second study of all cases of histological LS over the same period showed the incidence of SCC in vulval LS to be 7%.